2014
DOI: 10.1016/j.ejc.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Results and conjectures on simultaneous core partitions

Abstract: ABSTRACT. An n-core partition is an integer partition whose Young diagram contains no hook lengths equal to n. We consider partitions that are simultaneously a-core and b-core for two relatively prime integers a and b. These are related to abacus diagrams and the combinatorics of the affine symmetric group (type A). We observe that self-conjugate simultaneous core partitions correspond to the combinatorics of type C, and use abacus diagrams to unite the discussion of these two sets of objects.In particular, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 22 publications
0
127
0
1
Order By: Relevance
“…In this section we present four combinatorial descriptions for computing the zeta and eta maps, starting with an interpretation involving core partitions implicit in [1], followed by with an equivalent description via the sweep maps considered in [3]. Our main contributions are two new combinatorial descriptions of the zeta map involving interval intersections and a laser filling, along with the study of the eta map in all four contexts.…”
Section: The Zeta Map (And Eta)mentioning
confidence: 98%
See 3 more Smart Citations
“…In this section we present four combinatorial descriptions for computing the zeta and eta maps, starting with an interpretation involving core partitions implicit in [1], followed by with an equivalent description via the sweep maps considered in [3]. Our main contributions are two new combinatorial descriptions of the zeta map involving interval intersections and a laser filling, along with the study of the eta map in all four contexts.…”
Section: The Zeta Map (And Eta)mentioning
confidence: 98%
“…See, for example, [1][2][3]12], with equivalence of many definitions given in [3]. The precise description of zeta depends on making some choices; in our experience, these choices always resolve into one of two distinct maps, which we call zeta and eta.…”
Section: The Zeta Map (And Eta)mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, if π is the path on the left in Figure 23 This problem has been studied by Gorsky, Mazin, and Vazirani [GMV14] and Armstrong, Loehr, and Warrington [ALW14]. See also [AHJ14]. In [GMV14] it is shown that the sweep map is a bijection whenever m = kn + 1 or m = kn − 1 for some positive integer k. We note that in the case m = kn + 1 Loehr [Loe03], [Loe05b] (see also [Hag08][pp.…”
Section: Tesler Matrices and The Superpolynomialmentioning
confidence: 99%